Biological behavior of Trypanosoma cruzi stocks obtained from the state of Amazonas, Western Brazilian Amazon, in mice - Monteiro,Wuelton Marcelo (2012)
INTRODUCTION: The biological diversity of circulating Trypanosoma cruzi stocks in the Amazon region most likely plays an important role in the peculiar clinic-epidemiological features of Chagas disease in this area. METHODS: Seven stocks of T. cruzi were recently isolated in the State of Amazonas, Brazil, from humans, wild mammals, and triatomines. They belonged to the TcI and Z3 genotypes and were biologically characterized in Swiss mice. Parasitological and histopathological parameters were determined. RESULTS: Four stocks did not promote patent parasitemia in mice. Three stocks produced low parasitemia, long pre-patent periods, and a patent period of 1 day or oscillating parasitemia. Maximum parasitemia ranged from 1,400 to 2,800 trypomastigotes/0.1mL blood. Mice inoculated with the T. cruzi stocks studied showed low positivity during fresh blood examinations, ranging from 0% to 28.6%. In hemoculture, positivity ranged from 0% to 100%. Heart tissue parasitism was observed in mice inoculated with stocks AM49 and AM61. Stock AM49 triggered a moderate inflammatory process in heart tissue. A mild inflammatory process was observed in heart tissue for stocks AM28, AM38, AM61, and AM69. An inflammatory process was frequently observed in skeletal muscle. Examinations of brain tissue revealed inflammatory foci and gliosis in mice inoculated with stock AM49. CONCLUSIONS: Biological and histopathological characterization allowed us to demonstrate the low infectivity and virulence of T. cruzi stocks isolated from the State of Amazonas.